Strategy development: Driving improvisation in Malaysia - Hodgkinson, Ian R.; Hughes, Paul; Arshad, Darwina (Elsevier Ltd, 2015)
Improvisation is vital for strategy development, but there remains a lack of understanding about this phenomenon.This emerges directly from the insufficient investigation of its drivers and context.This paper extends improvisation research to the unexplored competitive settings of an emerging middle-income economy.Drawing on survey data from Malaysian research-intensive firms, we examine managerial and organisational antecedents of improvisation under turbulence.Findings reveal that organisational risk-taking and manager expertise are common antecedents of improvisation, but additional relationships arise under high (flexibility) and low turbulence (learning, manager tenure), developing capacity to inform practice, which is critically lacking in international business and management theory